Helminth-eating in grebes - Simmons, K E L (Wildfowl, 1975)
Great Crested Grebes Podiceps cristatus eat helminths, almost certainly tapeworms (Cestoda). These are extracted from the bird’s own cloaca or obtained from the water after defaecation, or obtained (directly or indirectly) from the parent and, at least occasionally, from the mate. Young grebes also show interest in their own helminths, from at least the age of about 45 days. It is possible that the habit is confined to certain localities, families, or individuals mainly because of differences either in the degree of local tapeworm infestation or in ’traditions’ arising out of the learning processes involved in the acquisition of the behaviour. Amongst adults, nearly all the records of helminth-eating and associated behaviour involved males. The types of tapeworm likely to be involved are reviewed and the biological value, or otherwise, of helminth-eating discussed, especially with reference to its possible nutritional value and to the possible harmful effects of recycling intact adult tapeworms. A record of helminth-eating is also given for the Red-necked Grebe P. grisegena, and the likelihood of the habit existing in other Podicepedidae discussed.